PERANCANGAN DAN IMPLEMENTASI APLIKASI BIMBINGAN DAN PENILAIAN TUGAS AKHIR BEBASIS ANDROID: STUDI KASUS STTI NIIT I-TECH - Efendi, Yasin; Hamdi Sukriyandi, Muhammad (Jurnal Ilmiah Sistem Informasi, 2024)
In practice, the final assignment guidance process does not always run smoothly, there are several obstacles that can cause the guidance process to not run smoothly, such as time and place constraints, namely where students and supervisors cannot always meet face to face to conduct guidance, there are also times when students want to do guidance but the guidance form is left behind or lost, and this is very disturbing because the guidance form is a record of the progress of compiling a final assignment which is a requirement for eligibility to advance to the trial, if these obstacles continue then there is a possibility that students will be hampered in compiling the final assignment. Time and place constraints can actually be overcome by utilizing email and chat messenger, but in terms of recording it remains an obstacle because it is not recorded in the guidance form. In this study, the author designed and implemented an application that can help with the above problems by creating an android-based application in which students and supervisors can interact and there are also recommendations for trials and final assignment grades for examiners